Synthesis and Characterization of 2-(5-mercapto-1,3,4- thiadiazol -2-yl)isoindoline-1,3-dione (L) and It’s Complexes with Some Transition Metals (Co(II) , Ni(II) , Cu(II) , Zn(II) and Cd(II) ) - et.al, Najat jawad Al-Obaidi (Al-Qadisiyah Journal of Pure Science, 2017)
In this work ,The ligand 2-(5-mercapto-1,3,4-thiadiazol-2-yl)isoindoline -1,3-dione (L) has been synthesized by the reaction of 5-amino -1,3,4-thiadiazole -2- thiol with phthalic anhydride by using fusion method . The metal complexes of the ligand were prepared with metals chlorides of Co(II) , Ni(II) , Cu(II) , Zn(II) and Cd(II) in ethanol as solvent . The ligand (L) and its metal complexes have been characterized by elemental analysis (CHN), IR, 1H-NMR and UV- Vis. spectra , magnetic susceptibility measurements , molar conductivity , melting points and atomic absorption . The metal-ligand ratio was determined by mole ratio method .The suggested structures for the Co(II) , Ni(II) and Cu(II) complexes are octahedral geometry and for the Zn(II) and Cd(II) complex are tetrahedral geometry .